Antidepressant therapy in patients with cardiovascular diseases - V. E. Medvedev; E. A. Korovyakova; V. I. Frolova; E. V. Gushanskaya (Неврология, нейропсихиатрия, психосоматика, 2019)
Depression is the most common form of mental illness in patients with cardiovascular diseases (CVD). Depression and CVD can worsen the clinical and dynamic characteristics of each other. The timely detection and adequate psychopharmacotherapy of depressive states in patients with CVD are of great clinical, therapeutic, and prognostic importance. Anti-antidepressant therapy promotes a more pronounced somatic stabilizing effect in patients with CVD. Adverse events to the use of antidepressants in patients with CVD may be associated with their negative effect on the hepatic cytochrome CYP450 isoenzymes involved in the metabolism of various drugs. The authors' own data of clinical psychopharmacotherapeutic studies and the results of meta-analyses indicate the high efficiency and good tolerability of agomelatine, an antidepressant with an innovative mechanism of action, in a wide range of patients